The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms22137035
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Two Differently Manufactured Silicon Dioxide Nanoparticles by Cloud Point Extraction Approach in Intestinal Cells, Intestinal Barriers and Tissues

Abstract: Food additive amorphous silicon dioxide (SiO2) particles are manufactured by two different methods—precipitated and fumed procedures—which can induce different physicochemical properties and biological fates. In this study, precipitated and fumed SiO2 particles were characterized in terms of constituent particle size, hydrodynamic diameter, zeta potential, surface area, and solubility. Their fates in intestinal cells, intestinal barriers, and tissues after oral administration in rats were determined by optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…NPs were reported to be more massively absorbed into the bloodstream than bulk-sized particles [ 26 , 27 ]. Our previous study also showed a higher intestinal transport amount of the precipitated SAS than the fumed SAS, using in vitro intestinal barrier models [ 22 ]. It should be noted that the oral absorption of SAS was less than 4%, even at 2000 mg/kg, and this finding is also in good agreement with the previous report [ 28 ].…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…NPs were reported to be more massively absorbed into the bloodstream than bulk-sized particles [ 26 , 27 ]. Our previous study also showed a higher intestinal transport amount of the precipitated SAS than the fumed SAS, using in vitro intestinal barrier models [ 22 ]. It should be noted that the oral absorption of SAS was less than 4%, even at 2000 mg/kg, and this finding is also in good agreement with the previous report [ 28 ].…”
Section: Resultsmentioning
confidence: 98%
“…The hydrodynamic diameters (375 ± 1 nm) of precipitated SAS in distilled water (DW) were significantly larger than those (156 ± 1 nm) of fumed SAS ( Supplementary Figure S2B ), suggesting high aggregate formation of the former in DW. It is worth noting that precipitated SAS was determined to be less aggregated than fumed SAS in cell culture minimum essential medium and three consecutive steps of the GI fluid ( Figure S2B ) [ 22 ], indicating different aggregate states of SAS depending on the biological environment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations